The Effect of Self-Talk and Feedback on Acquisition and Retention of Basketball Chest Pass - Mina Emami Arandi; Ali Akbar Jaberi Moghaddam; Ahmad Farokhi (University of Tehran, 2018)
The aim of this study was to compare the effect of self-talk (ST), feedback (KP) and their interaction (STF) on acquisition and retention of basketball chest pass. 120 adolescent girls were selected and randomly assigned to 4 groups: KP, ST, ST + KP and control. This study was semi-experimental and pretest-posttest design with a control group. Instructional self-talk and knowledge of performance feedback were used in this study. After the pretest, each group had 4 practice sessions in the acquisition phase; then, they had posttest and 72 hours later they had retention test. One-way ANOVA and Tukey post hoc test were used to analyze data. Results indicated those subjects who used ST achieved better acquisition and retention scores than the other groups (P<0.05). ST was more effective than KP in the acquisition of chest pass skill. ST and KP can lead to a better and faster development of learning in the early phases